Authentic Leadership Questionnaire aplicado a enfermeiros brasileiros: evidências de validade - Maziero, Vanessa Gomes; Rocha, Fernanda Ludmilla Rossi; Campos, Juliana Alvares Duarte Bonini [UNESP]; Dias, Bruna Moreno; Balsanelli, Alexandre Pazetto; Gabriel, Carmen Silvia; Bernardes, Andrea (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to establish the psychometric properties of the Authentic Leadership Questionnaire (ALQ) applied to Brazilian nurses. METHOD: cross-sectional observational study with a non-probabilistic sample. The psychometric properties of the RATER and SELF versions of the ALQ were calculated using confirmatory factor analysis with the WLSMV robust estimation method. The following indices were used to assess the goodness-of-fit of the model: chi-square by degrees of freedom (χ2/df), Tucker-Lewis Index (TLI), Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA) and Standardized Root Mean Squared Residual (SRMR). Data reliability was analyzed using the ordinal coefficient alpha and composite reliability. RESULTS: 181 nurses participated of the study (female gender: 80.1%; mean age of 34.6 years; working time of less than five years: 76.3%). The complete ALQ RATER and ALQ SELF models did not present an adequate fit. Therefore, the refined models presented a better fit to the sample data (ALQ RATER: χ2/df=2.77; CFI=0.97; TLI=0.97; RMSEA=0.10; SRMR=0.05; ALQ SELF: χ2/df=2.74; CFI=0.94; TLI=0.92; RMSEA=0.10; SRMR=0.08). In the ALQ RATER model, items 1, 7 and 13 were excluded. Due to the high correlation between the factors Relational Transparency and Moral Perspective, a three-factor model based on the combination of the factors mentioned above was proposed. In the ALQ SELF model, items 2, 5, 9 and 10 were excluded. Likewise, a three-factor model based on the combination of two factors, now called Self-Awareness Balance, was proposed. CONCLUSION: the data obtained with the Authentic Leadership Questionnaire with Brazilian nurses were valid and reliable.

OBJETIVO: estimar las propiedades psicométricas del Authentic Leadership Questionnaire (ALQ) aplicado a enfermeros brasileños. MÉTODO: estudio observacional transversal con muestreo no probabilístico. Las propiedades psicométricas de las versiones RATER y SELF del ALQ se estimaron mediante análisis factorial confirmatorio con el método de estimación robusta WLSMV. Como índices de calidad de ajuste de los modelos se utilizó: razón de chi-cuadrado por grados de libertad (χ2/gl), Tucker-Lewis Index (TLI), Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA) y Standardized Root Mean Squared Residual (SRMR). La confiabilidad de los datos se analizó mediante el coeficiente alfa ordinal y la confiabilidad compuesta. RESULTADOS: participaron 181 enfermeros (sexo femenino: 80,1%; edad media de 34,6 años; tiempo de trabajo inferior a cinco años: 76,3%). Los modelos completos ALQ RATER y ALQ SELF no mostraron un ajuste adecuado. Por lo tanto, el modelo refinado presentó un mejor ajuste para la muestra (ALQ RATER: χ2/gl=2,77; CFI=0,97; TLI=0,97; RMSEA=0,10; SRMR=0,05; ALQ SELF: χ2/gl=2,74; CFI=0,94, TLI=0,92, RMSEA=0,10, SRMR=0,08). En el modelo ALQ RATER se eliminaron los ítems 1, 7 y 13. Debido a la alta correlación entre los factores Transparencia Relacional y Perspectiva Moral, se propuso un modelo de tres factores basado en la unión de los factores mencionados anteriormente. En el modelo ALQ SELF se eliminaron los ítems 2, 5, 9 y 10. Asimismo, se propuso un modelo trifactorial basado en la unión de dos factores, ahora denominado Equilibrio de Autoconciencia. CONCLUSIÓN: los datos obtenidos con el Authentic Leadership Questionnaire con enfermeros brasileños fueron válidos y confiables.

OBJETIVO: estimar as propriedades psicométricas do Authentic Leadership Questionnaire (ALQ) aplicado a enfermeiros brasileiros. MÉTODO: estudo observacional transversal com amostragem não probabilística. As propriedades psicométricas das versões RATER e SELF do ALQ foram estimadas utilizando-se análise fatorial confirmatória com método de estimação robusto WLSMV. Como índices de qualidade de ajustamento dos modelos, foram utilizados: razão do qui-quadrado pelos graus de liberdade (χ2/gl), Tucker-Lewis Index (TLI), Comparative Fit Index (CFI), Root Mean Square Error of Aproximation (RMSEA) e Standardized Root Mean Squared Residual (SRMR). A confiabilidade dos dados foi analisada por meio do coeficiente alfa ordinal e da confiabilidade composta. RESULTADOS: participaram 181 enfermeiros (sexo feminino: 80,1%; média de idade de 34,6 anos; tempo de trabalho inferior a cinco anos: 76,3%). Os modelos completos da ALQ RATER e ALQ SELF não apresentaram ajustamento adequado. Porquanto, o modelo refinado apresentou melhor ajustamento para a amostra (ALQ RATER: χ2/gl=2,77; CFI=0,97; TLI=0,97; RMSEA=0,10; SRMR=0,05; ALQ SELF: χ2/gl=2,74; CFI=0,94; TLI=0,92; RMSEA=0,10; SRMR=0,08). No modelo ALQ RATER, foram removidos os itens 1, 7 e 13. Devido à alta correlação entre os fatores Transparência Relacional e Perspectiva Moral, foi proposto um modelo trifatorial com base na junção dos fatores acima citados. No modelo ALQ SELF, foram retirados os itens 2, 5, 9 e 10. Do mesmo modo, foi proposto um modelo trifatorial baseado na junção de dois fatores agora denominado Equilíbrio Autoconsciência. CONCLUSÃO: os dados obtidos com Authentic Leadership Questionnaire com enfermeiros brasileiros foram válidos e confiáveis.
Authentic Leadership Questionnaire applied to Brazilian nurses: evidence of validity